Stock investing for dummies - Mladjenovic, Paul J (Hoboken, N.J. : Wiley ; Chichester : John Wiley & Sons, 2013)
This practical guide gives you proven strategies for selecting and managing profitable investments in either a bear or bull market. Discover how to navigate the new economic landscape, and choose the right stocks for different situations.
The fast and easy way to grow your stock investments in today's changing market The changes, events and conditions affecting stock investors since the recent economic crisis have been dramatic. Today's economic and financial landscape offers new challenges and opportunities for investors and money managers. This new edition of Stock Investing For Dummies provides you with the information you need to protect and grow your stock investments in today's changing market. Stock Investing for Dummies contains 25 percent new and revised material designed to help investors navigate an ever-changing stock market with: information on ETFs, a safer way to be more diversified in the stock market; new rules, exchanges, and investment vehicles; the latest on the European debt crisis; and much more. The book explores how technological changes mean new products, services, and ways of doing business. It shows you how to use the latest research and information available, and it covers how (and why) to protect yourself.
Introduction -- The essentials of stock investing -- Before you start buying -- Picking winners -- Investment strategies and tactics -- The part of tens.
Previous ed.: 2009.
Includes index.
Keywords: Stocks; Investments